(untitled) (Research, Society and Development, 2022)
Cashew leaf extracts have been shown to be effective in the treatment of diseases and also do not allow the proliferation of microorganisms, such as fungi and bacteria. However, in Brazil, leaves have not had their deserved prominence, since most agricultural producers consider tree pruning as a waste, since the industry, in general, does not recognize its relevance due to applications and properties. The objective of this study was to identify the secondary metabolites of the hydroethanolic extract of the leaf of Anacardiumoccidentale L., through a qualitative method of precipitation. The extract showed positive results for the following metabolites: alkaloids, tannins, steroids/triterpenes. Thus, the extract has the potential to be explored as a phytotherapic.